Peran Ekonomi Mikro Islam Dalam Mendukung Keberlanjutan UMKM Halal di Indonesia - Sitorus, Satrio Setiawan; Hasibuan, Reni Ria Armayani; Arinda, Gistrant Yoga (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Islamic microeconomics is now increasingly important to support halal small and medium enterprises (SMEs) in Indonesia. These halal SMEs not only help the family economy, but also protect religious values and business sustainability. This article explores how Islamic microeconomics can help halal SMEs to survive and grow. With a qualitative approach, data were drawn from interviews and literature studies. As a result, the Islamic microeconomy provides Shariah-compliant funding solutions, education, and a strong business network. This makes halal SMEs survive in an increasingly tight market.